Anticipatory Guidance for Teens with Diabetes as They Transition to Adulthood. - Severson, Lynn L. (My University, 2009)
This project focused on the development of a tool, combining research and practice, that could improve self-management for teens and young adults with diabetes.
Color poster with text and images.
Keywords: Diabetics--Life skills guides; Diabetics--Services for; Diabetics--Counseling of; Young adults--Diseases--Services for; Young adults--Counseling of; Posters